DGGE coupled with ribosomal DNA gene phylogenies reveal uncharacterized fungal phylotypes - Duong L.M. (2014)
Most fungal diversity studies have previously been based on morphological examination and cultivation methods. In this study we use a molecular method based on DGGE coupled with sequence analysis of 18S rRNA gene to assess fungal diversity on leaves of Magnolia liliifera. To achieve this, we extracted total genomic DNA and used fungal specific primers (NS1 and GCFung) to obtain fungal sequences. PCR-DGGE analysis recovered 14 operational taxonomic units (OTU) from different parts of the studied leaves. Phylogenetically, 8 OTUs belonged to the order Pleosporales and other bitunicate ascomycetes; 2 and 3 were related to the Xylariaceae, (Xylariales) and Hypocreales, respectively; 1 OTU was phylogenetically affiliated with the Rhytismatales. While this molecular approach identified taxa that were not recovered from morphological or cultural studies, it did not detect other taxa that were predominantly isolated using traditional methods. The three different parts of one leaf tested (petioles and midribs, leaf blade lower and upper parts) yielded different fungal taxa that possible indicate tissue-recurrence. The findings are compared with previous studies on the same host where endophytes were investigated using traditional culturing techniques.